Investigating the Environmental Impacts of Landmines in the Maidan Sub-district through GIS-Based Mapping - Azeez, Hoshmand Ahmed Azeez; Sadradin, Kazim Ahmed Sadradin; Azeez, Shkar Ahmed Azeez (Sulaimani Journal for Humanities, 2025)
Landmines and explosive remnants of war (ERW) create serious threats to human safety and the environment. Decades of armed conflict have resulted in widespread landmine contamination in Iraq, severely affecting ecosystems and land use. The Maidan sub-district in particular remains heavily contaminated and requires detailed spatial analysis to assess both the extent and the environmental consequences of landmine presence. This study used a GIS-based mapping approach to identify and visualize the spatial distribution of contaminated areas in the Maidan sub-district. Data provided by the Mine Action Agency (MAA) of the Kurdistan Regional Government (KRG), collected using Garmin GPS and Trimble devices, were integrated into ArcGIS Pro for analysis. The total contaminated land area (in square meters) was calculated, and mine-affected sites were classified into categories to support statistical and spatial interpretation. The findings revealed that landmine contamination has significantly degraded local ecosystems by restricting vegetation regrowth, fragmenting habitats, and preventing the safe use of land for agriculture, grazing, and various forms of human activity. Several previously productive agricultural zones are now unusable due to persistent contamination. Furthermore, environmental degradation was observed in the form of reduced biodiversity and limited natural land recovery in affected areas. GIS mapping proved effective in delineating mined zones, quantifying contaminated land, and visualizing patterns of environmental impact. This spatial analysis enables more targeted mine clearance operations and supports post-conflict recovery efforts. Ultimately, the study demonstrates how GIS-based environmental assessment can inform land-use planning, ecological restoration, and policy decision-making in post-conflict regions like Maidan.
Keywords: Landmines; environmental impacts; GIS; Maidan subdistrict